1998
DOI: 10.1002/(sici)1096-9861(19980413)393:3<267::aid-cne1>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of basal optic tract terminals in the turtle, Pseudemys scripta elegans

Abstract: The morphologies of axon terminals of retinal ganglion cells projecting to the basal optic nucleus (BON) via the basal optic tract (BOT) were studied in the red-eared turtle. The BOT was visualized on the ventral surface of the brainstem in vitro, and either biotinylated dextran amine was injected extracellularly or neurobiotin was injected into physiologically identified axons during intracellular recordings. Up to 16 hours after tracer injection, the brains were fixed, sectioned parasagittally, and stained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The turtle cerebellum can be isolated and maintained in a physiological state as an in vitro preparation allowing stabilized iontophoretic ejections and intraaxonal transport (Martin et al 1998). Thirteen pond turtles (Pseudemys scripta elegans) were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The turtle cerebellum can be isolated and maintained in a physiological state as an in vitro preparation allowing stabilized iontophoretic ejections and intraaxonal transport (Martin et al 1998). Thirteen pond turtles (Pseudemys scripta elegans) were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Also, labeling neurons during whole-cell recordings has dem- Martin et al, 1998) is also shown in its position within a BON. Also, labeling neurons during whole-cell recordings has dem- Martin et al, 1998) is also shown in its position within a BON.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that BOT axon terminals spread throughout the rostrocaudal extent of the BON where varicosities and terminal boutons often formed clusters within regions of 150 mm 3 or less and that these sites presumably provide synaptic contact with BON cells (Martin et al, 1998). The turtle BOT is the singular path of direct retinal input.…”
Section: Retinal Inputsmentioning
confidence: 99%
See 2 more Smart Citations